SYNTHESIS, ANTIMICROBIAL EVALUATION, DENSITY FUNCTIONAL THEORY, AND DOCKING STUDIES OF SOME NEW 2-MERCAPTO PYRIMIDINE SCHIFF BASES - AL-JUBOORI, SAHAR B.; MAHMOOD, AMMAR A. RAZZAK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Pyrimidine derivatives are reported to possess antibacterial, antifungal, anticancer, and anticonvulsant activities. Encouraged by this remarks, we decided to synthesize novel compounds of new 2-macraptopyrimidine linked to Schiffs̕ bases. Methods: The present work involves the synthesis of new 2-mercaptopyrimidine linked to Schiffs̕ bases. The starting, 2-mercaptopyrimidine, compound (1) reacted with thiourea to afford the corresponding 1-(pyrimidin-2-yl) thiourea (2). Then compound (2) was used as the key intermediate to prepare the -1-(2-hydroxy benzylidene)-3-(pyrimidin-2-yl) thiourea (3), and (1-benzylidine)-3-(pyrimidin-2-yl) thiourea (4), through the reaction with 2-hydroxybenzaldehyde, and benzaldehyde, respectively. Results: All the synthesized compounds were characterized by Fourier-transform infrared and1H-nuclear magnetic resonance spectroscopy. The synthesized derivatives were screened for their in vitro, antibacterial activity against two Gram-positive bacteria: Bacillus subtilis and Staphylococcus aureus and four Gram-negative bacteria: Klebsiella pneumoniae, Escherichia coli, and Salmonella typhi, and the results showed that most of them have good antibacterial activity. While their antifungal activity against three fungi species (Aspergillus fumigates, Aspergillus niger, Aspergillus terrus and Rhizopus) revealed that compounds (2-4) displayed the most potent antifungal activity. Density functional theory (DFT) calculations for the synthesized 2-mercapto pyrimidine derivatives were conducted, using a molecular structure with optimized geometry. Highest occupied molecular orbital/lowest unoccupied molecular orbital energies and structures are demonstrated. Conclusion: The antimicrobial activity indicates that compounds (3) and (4) are the most active than the compounds (1) and (2). Molecular docking revealed that compounds (3) and (4), with bulky phenyl groups are essential to blocking the active centers of glucose -6-phosphate synthase in the bacteria and fungi.